Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1210/jc.2017-00039
|View full text |Cite
|
Sign up to set email alerts
|

Association of Directly Measured Plasma Free 25(OH)D With Insulin Sensitivity and Secretion: The IRAS Family Study

Abstract: Our data showed that plasma free 25(OH)D had a slightly stronger association with SI compared with plasma total 25(OH)D, although the difference was modest and there were no marked differences in the associations between Hispanics and African Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Lee et al observed that free and total 25(OH)D were positively associated with tissue insulin sensitivity index and β-cell function among nondiabetic subjects. However, after adjustment for BMI, only free 25(OH)D was significantly associated with insulin secretion [55]. In our study, the associations between different forms of 25(OH)D (total, free and bioavailable) and T2D remained statistically significant after adjustment for BMI (0.95, CI 95% 0.93-0.97; 0.95, CI 95% 0.91-0.99; 0.88, CI 95% 0.78-0.99; respectively).…”
Section: Discussionmentioning
confidence: 89%
“…Lee et al observed that free and total 25(OH)D were positively associated with tissue insulin sensitivity index and β-cell function among nondiabetic subjects. However, after adjustment for BMI, only free 25(OH)D was significantly associated with insulin secretion [55]. In our study, the associations between different forms of 25(OH)D (total, free and bioavailable) and T2D remained statistically significant after adjustment for BMI (0.95, CI 95% 0.93-0.97; 0.95, CI 95% 0.91-0.99; 0.88, CI 95% 0.78-0.99; respectively).…”
Section: Discussionmentioning
confidence: 89%
“…In non-bone health association studies, the results have been mixed. In some studies free serum 25(OH)D levels were inversely associated with coronary artery disease (125), pediatric inflammatory bowel disease (126) and ulcerative colitis (127), insulin sensitivity (128), reduction in lipid markers in statin patients (129), and acromegaly (130). However, in some other studies free 25(OH)D was inferior in asthma (131) and no better than total 25(OH)D for colorectal cancer in African-Americans (132).…”
Section: Human Studies Of Free 25(oh)dmentioning
confidence: 99%
“…However, both studies were underpowered for detection of minor effects. And finally, the effect of giving vitamin D to subjects with established T2DM do at best show a marginal effect on HbA 1c with a reduction of 0.32% in HbA 1c as compared with placebo according to a review by Lee et al that included nine trial with 3,324 participants (35).…”
Section: T2dmmentioning
confidence: 99%